Main directions of economic growth of modern Georgia - Ushangi Samadashvili (Theoretical Hypotheses and Empirical Results, 2023)
The article substantiates that long-term economic growth is necessary for the continuous improvement of the living standards of the population of Georgia. For long-term economic growth, the following are important: predictable political and economic stability; law supremacy; growing demand; large long-term foreign investments; Modernization of the national economy, symmetrical development in the sectoral-regional aspect and multi-vector approach; Protection and development of infrastructure and its main component - human capital; formation of a culture of inheritance in the implementation of economic policy; Harmonization of Georgian legislation with EU legislation to enter the EU market; increase in the number, types, quality, safety and security of Georgian export products; introduce products to customers in prospective foreign markets, create a desire to buy and position them positively in their minds. Introducing Georgian products to clients in prospective foreign markets, approving them, forming a desire to purchase and positioning them positively in their consciousness.